2021
DOI: 10.37358/mp.21.3.5509
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Tribological Performance of Self-Cured Poly Methyl Methacrylate Reinforced by Alumina Nanowires and Zirconia Nanoparticles for Denture Applications

Abstract: Polymethyl methacrylate (PMMA) is one of the common widely accepted biomaterials in prosthetic dentistry due to its acceptable advantages, since 1937. In the present work, PMMA reinforced with Al2O3 nanowires (Al2O3 NWs) and ZrO2 nanoparticles (ZrO2 NPs) were fabricated by a self-curing method. Mechanical and tribological tests were conducted to study the effect of nanofillers on the mechanical and tribological performance of PMMA nanocomposites. Compression and microhardness tests, as mechanical tests, were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Based on the results shown in Fig. 5 , the best parameter settings are 1.2 wt% for the DSNP filler at a normal load of 10 N. These settings are in good agreement with earlier reported results 39 , 42 , 44 . On the other hand, friction resistance decreased with the addition of the DSNP and TiO 2 NP fillers at up to 1.5 wt%.…”
Section: Resultssupporting
confidence: 90%
“…Based on the results shown in Fig. 5 , the best parameter settings are 1.2 wt% for the DSNP filler at a normal load of 10 N. These settings are in good agreement with earlier reported results 39 , 42 , 44 . On the other hand, friction resistance decreased with the addition of the DSNP and TiO 2 NP fillers at up to 1.5 wt%.…”
Section: Resultssupporting
confidence: 90%
“…Soft materials are defined as polymers having hardness values lower than 65. In addition to being employed in automotive applications, soft polymeric materials offer flexible electrical uses 32,40 …”
Section: Resultsmentioning
confidence: 99%
“…In addition to being employed in automotive applications, soft polymeric materials offer flexible electrical uses. 32,40…”
Section: Hardnessmentioning
confidence: 99%
“…Nowadays, nanotechnology has been applied in dental applications in which various researches have been employed to overcome the mechanical performance drawbacks of denture base materials, [12]. Several researches have been focused on enhancing of PMMA properties in all curing methods by incorporation of nanofillers in its composition, [13,14]. Homogenous distribution of reinforcement material, as a filler in the nanometer scale, in PMMA, as matrix material, and interfacial interaction between them, led to improve the nanocomposites properties, [15,16].…”
mentioning
confidence: 99%
“…Among these additives, ZrO2 NPs are known for their inherent suitable properties. Previous studies emphasized an enhancement of the physical and mechanical properties of PMMA/ZrO2 nanocomposite for denture base materials application, [14,22]. It was found that adding of 3-5 wt.…”
mentioning
confidence: 99%